Un corso innovativo in cui Chimica e Scienza della Complessità preparano le nuove generazioni ad affrontare le sfide globali del XXI secolo - Gentili, Pier Luigi (Chimica nella Scuola, 2024)
In the 21st century, humanity is spurred to face global challenges. Global challenges can be won if we prepare the new generations to deal with Complex Systems. Therefore, it is urgent that chemistry is integrated with the Science of Complexity and interdisciplinary courses on Complex Systems are proposed at the University and in Schools.